2021
DOI: 10.3389/fpsyg.2021.784907
|View full text |Cite
|
Sign up to set email alerts
|

Twitter Mediated Sociopolitical Communication During the COVID-19 Pandemic Crisis in India

Abstract: While Twitter has grown popular among political leaders as a means of computer-mediated mass media communication alternative, the COVID-19 pandemic required new strategies for socio-political communication to handle such a crisis. Using the case of India, which was one of the worst-hit countries and is also the world’s largest democracy, this research explicates how political leaders responded to the COVID-19 crisis on Twitter during the first wave as it was the first time such a crisis occurred. Theoretical f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In addition to being used as a tool for communication, social media also serves as a very successful platform in various other areas, including public administration, higher education, product marketing, and customer relationship IAPA 2022 management [3]. Many ideas have been raised on social media, especially concerning interesting contemporary issues that have been frequently discussed on Twitter, like COVID-19 [4][5] that affected many sectors of our daily life [6] [7]. Several public policies, particularly those relating to the treatment of COVID-19, have finally been acknowledged by social media users, leading to discourses that are highly sought after by all social media users [8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to being used as a tool for communication, social media also serves as a very successful platform in various other areas, including public administration, higher education, product marketing, and customer relationship IAPA 2022 management [3]. Many ideas have been raised on social media, especially concerning interesting contemporary issues that have been frequently discussed on Twitter, like COVID-19 [4][5] that affected many sectors of our daily life [6] [7]. Several public policies, particularly those relating to the treatment of COVID-19, have finally been acknowledged by social media users, leading to discourses that are highly sought after by all social media users [8].…”
Section: Introductionmentioning
confidence: 99%
“…The first case of COVID-19 in India was reported on 30th January 2020. After it was declared as a pandemic by the WHO, on 19th March 2020, the Indian Prime Minister Narendra Modi addressed the nation on the issue of the pandemic calling for a self-imposed curfew on 22nd March, so as to prepare the citizens for the coming days (Jain et al, 2021). It has been noted that a strong national identity is useful as leverage when you are seeking to garner favors for sound public health, and precautionary actions for the benefit of the larger population (Van Bavel et al, 2020).…”
Section: The Covid-19 Scenario In Indiamentioning
confidence: 99%
“…Information posted by official sources that has been verified is key to establishing credibility and trust among citizens [ 26 ], but the COVID-19 infodemic resulted in the frequent sharing of misleading information and false claims, such as the sharing of pseudo-scientific therapies, and discussions about the origin and spread of the disease [ 27 ]; these activities can undermine public trust in governments. A previous study in India found that focusing on Twitter sentiment was an important crisis management strategy [ 28 ]. Therefore, to reduce the harm caused by public health crises, government agencies and public health organizations can use social media to help deal with the dissemination of crisis information [ 29 ].…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%